Int J Plant Sci Hor 2020
DOI: 10.36811/ijpsh.2020.110022
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of certain pesticides and their alternatives against the black vine thrips, Retithrips syriacus (Mayet) (Thysanoptera: Thripidae) infesting grapevine

Abstract: The black vine thrips, Retithrips syriacus Mayet (Thripidae: Thysanoptera) is considered as pest. Adults and nymphs of this pest causes a serious damage to grapevine leaves. The experiments were carried out to evaluate the toxicity of seven pesticides on nymphs and adults of GVT on Flame seedless and Superior commercial vineyard varieties under laboratory and field conditions during 2016/2017 season. Data clearly indicate that the order of efficiency of the tested compounds were the same at both LC50 and LC90 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
0
0
Order By: Relevance
“…for B. bassiana and M. anisopliae isolates. Allam et al (2020) stated that spinetoram was the most toxic compound against the black vine thrips with LC 50 and LC 90 values of 0.1 and 0.87 ppm, respectively, however, the lower toxicity was observed for KZ oil and garlic extract. Also, our results were found in the same line with those obtained by Chen et al (2022), Kilaso (2022) and Rao et al (2022).…”
Section: Efficacy Of Insecticides Against Onion Thrips T Tabaci In Th...mentioning
confidence: 98%
See 1 more Smart Citation
“…for B. bassiana and M. anisopliae isolates. Allam et al (2020) stated that spinetoram was the most toxic compound against the black vine thrips with LC 50 and LC 90 values of 0.1 and 0.87 ppm, respectively, however, the lower toxicity was observed for KZ oil and garlic extract. Also, our results were found in the same line with those obtained by Chen et al (2022), Kilaso (2022) and Rao et al (2022).…”
Section: Efficacy Of Insecticides Against Onion Thrips T Tabaci In Th...mentioning
confidence: 98%
“…For safe materials, only chili extract gave reduction > 50%, with mean reduction percentage of 51.06% in 2021/2022 season. Many investigators studied the control of thrips by synthetic insecticides, (Allam et al, 2020;Negash et al, 2020;Khan et al, 2022;Nadeem et al, 2022;Geremias et al, 2022;Ihsan et al, 2022), they reported that spinetoram, emamectin benzoate and pyridalyl were the most effective against T. tabaci. The effect of alternative materials as safe compounds for onion thrips control has been studied by many authors.…”
Section: Efficacy Of Insecticides Against Onion Thrips T Tabaci In Th...mentioning
confidence: 99%